Overview of Workload on Anesthesians in The Banyumas Region - Putri, Putri Adawia; Lintang Suryani, Roro; Bisma Yudha, Magenda (Global Indonesia Health Care (GOICARE), 2025)
Background: Workload is, by definition, that which involves the existence of certain tasks imposed with certain deadlines; excess performance may sometimes lead to boredom. Life in an intensive care unit and operating room is quite labor-intensive. Interpersonal skill management is crucial for anesthetists in maintaining efficiency and avoiding burnout. Stress and tension are brought about by workloads, and indeed anesthetists experience some bodily and mental fatigue in performing their jobs. The administrators of anesthesia are health care personnel charged with overseeing the anesthetic care of a patient during anesthesia management, which includes before, during, and after anesthesia. Purpose: The aim of this study was to evaluate the workload of anesthetists working in the Banyumas area. Methods: The descriptive survey design in its combination of qualitative and quantitative approaches casts upon a cross-sectional design of this study. A total of 47 respondents were taken as samples; a complete sampling method was adopted. A specifically designed questionnaire was administered to respondents for data collection constituting 12 closed-ended questions. Results: It was found that three participants (6.4%) reported no workload, ten participants (21.3%) were considered to be under light workload, twenty-five participants (53.2%) worked under medium workload conditions, and nine participants (19.1%) were given heavy workload. Conclusion: In general, anesthetists working in the central surgical installation room at Banyumas District Hospital are assessed to be under a light workload.